Spectral ripple discrimination and use of speech context factors in relation to speech perception in noise in single-sided deaf cochlear implant users. - van Heteren, Jan A. A.; Smit, Adriana L.; Stokroos, Robert J.; Rhebergen, Koenraad S. (International Journal of Audiology, 2026)
Objective: To investigate the relation between spectral ripple discrimination and speech perception in noise in single-sided deaf (SSD) cochlear implant (CI) users, and to investigate the use of speech context in speech perception in noise, for both the normal-hearing (NH) and the CI ear. Design and study sample: Twenty adult SSD CI users (40 ears) participated in the study. We used the spectral-temporally modulated ripple test (SMRT) and measured speech reception thresholds (SRTs) with the consonant-vowel-consonant (CVC)-in-noise test, the hearing-in-noise (sentence) test (HINT), and the digits-in-noise (DIN) test. The use of speech context was explored by calculating j and s factors. Results: The SMRT scores were significantly correlated to the CVC, HINT, and DIN SRTs for the CI ears but not for the NH ears. No significant differences or correlations between the j and s speech context factors for the NH ear and CI ear were found. Only the CVC SRTs and the CVC context factors for the NH ears were significantly correlated. Conclusion: The SMRT can be of added value in the evaluation of hearing performance of SSD CI users. The SSD patients utilised speech context to a similar degree with both the NH ear and the CI ear.